2016
DOI: 10.2147/ijn.s109062
|View full text |Cite
|
Sign up to set email alerts
|

Eupafolin nanoparticles protect HaCaT keratinocytes from particulate matter-induced inflammation and oxidative stress

Abstract: Exposure to particulate matter (PM), a major form of air pollution, can induce oxidative stress and inflammation and may lead to many diseases in various organ systems including the skin. Eupafolin, a flavonoid compound derived from Phyla nodiflora , has been previously shown to exhibit various pharmacological activities, including antioxidant and anti-inflammatory effects. Unfortunately, eupafolin is characterized by poor water solubility and skin penetration, which limits its clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…The fact that IL-1β is secreted in acne skin condition has proposed valuable effects of IL-1β-targeted therapy in patients suffering from anti-inflammatory acne-lesions [ 24 , 26 ]. P. acnes is able to induce the secretion of chemokine CXCL8 in monocytes and keratinocyte [ 25 , 26 ]. We also observed that the mRNA expression levels of cytokines in P. acnes -induced THP-1 cells were decreased by ES treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that IL-1β is secreted in acne skin condition has proposed valuable effects of IL-1β-targeted therapy in patients suffering from anti-inflammatory acne-lesions [ 24 , 26 ]. P. acnes is able to induce the secretion of chemokine CXCL8 in monocytes and keratinocyte [ 25 , 26 ]. We also observed that the mRNA expression levels of cytokines in P. acnes -induced THP-1 cells were decreased by ES treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our in vivo results, we observed the anti-inflammatory effects of ES in P. acnes -treated animal model. Several studies have described that injection of live P. acnes can lead to the development of inflammatory skin disease in ear-inflammation model [ 26 ]. These studies have demonstrated that live P. acnes treated group has roughly 2 fold increase in ear thickness compared to PBS treated ear [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [23] and it can be a reliable differentiation model to estimate the inflammatory and repair response, as well as a cell platform for the development of novel treatments and the investigation of disease mechanisms [5,[24][25][26][27][28]. In our The HaCaT cell line was first generated by Boukamp et.…”
Section: Introductionmentioning
confidence: 99%
“…[23] and it can be a reliable differentiation model to estimate the inflammatory and repair response, as well as a cell platform for the development of novel treatments and the investigation of disease mechanisms [5,[24][25][26][27][28]. In our previous study [27,29], we prepared water-soluble 7, 3 , 4 -trihydroxyisoflavone NPs by using the planetary ball mill method [27] and eupafolin NP delivery system [25,29] to investigate their individual antioxidant and anti-inflammatory activities in PM-induced skin inflammation [5,24,25,29]. The results of our previous study suggested that PM-induced skin cell inflammation regulated the AhR/p47 phox/NADPH oxidase pathway, and subsequently increased ERK1/2, p38/nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), and c-Jun N-terminal kinase (JNK)/Activator protein 1 (AP-1) levels [5].…”
Section: Introductionmentioning
confidence: 99%